2003
DOI: 10.1200/jco.2003.09.534
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise in Men Receiving Androgen Deprivation Therapy for Prostate Cancer

Abstract: Resistance exercise reduces fatigue and improves quality of life and muscular fitness in men with prostate cancer receiving androgen deprivation therapy. This form of exercise can be an important component of supportive care for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
683
5
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 701 publications
(748 citation statements)
references
References 37 publications
31
683
5
10
Order By: Relevance
“…All seven group-based exercise studies 4,58,59,61,62,65,66 tended to show significant improvements in at least two of the three domains of physical fitness assessed, namely muscular strength, muscular endurance and aerobic endurance. In contrast, only two of the four home-based studies that assessed physical fitness measures found any significant improvements, and these were only observed for aerobic endurance 51,64 .…”
Section: Resultsmentioning
confidence: 96%
“…All seven group-based exercise studies 4,58,59,61,62,65,66 tended to show significant improvements in at least two of the three domains of physical fitness assessed, namely muscular strength, muscular endurance and aerobic endurance. In contrast, only two of the four home-based studies that assessed physical fitness measures found any significant improvements, and these were only observed for aerobic endurance 51,64 .…”
Section: Resultsmentioning
confidence: 96%
“…Inclusion criteria included type 2 diabetes mellitus as defined by the American Diabetes Association [13] for at least 6 months and baseline HbA 1c of 6.6% to 9.9%. Potential participants were excluded if they: (1) were receiving insulin therapy; (2) were participating in exercise ≥2 times per week for at least 20 min per session or had been in any resistance training during the previous 6 months; (3) reported changes in oral hypoglycaemic medications during the previous 2 months; (4) reported changes in antihypertensive or lipidlowering agents in the previous month; (5) reported a change of ≥5% in body weight during the previous 2 months; (6) had serum creatinine ≥200 μmol/l; (7) had proteinuria >1 g/24 h; (8) had blood pressure >160/95 mmHg; (9) had restrictions in physical activity due to disease; (10) had other medical conditions making participation inadvisable; or (11) completed fewer than ten of the 12 scheduled exercise sessions during the run-in period.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies, however, have reported particularly beneficial effects of resistance exercise training on these outcomes in other clinical populations including patients with cardiac disease [9], the frail elderly [10] and men with prostate cancer receiving androgen deprivation therapy and/or radiotherapy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Segal et al 57 studied the effects of resistance exercise training on muscle strength and QOL in men with PC. Specifically, 155 men diagnosed with PC who were undergoing ADT were randomized to an exercise group or a control group.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
“…They found that participants in the exercising group were more likely to have increased upper and lower body strength, increased QOL measures and decreased fatigue as compared to men in the control group. 57 In a similar study, 66 patients with PC receiving radiation therapy were randomized to an exercise intervention group or a control group. In this study, the exercise intervention was home-based aerobic exercise therapy three times weekly for 16 weeks.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%